ROLE OF EARLY CPAP THERAPY IN ACUTE DECOMPENSATED HEART FAILURE IN EMERGENCY SETTING (The Research of Medical Science Review, 2025)
Objective: To evaluate the impact of early Continuous Positive Airway Pressure (CPAP) therapy on clinical outcomes in patients with Acute Decompensated Heart Failure (ADHF) in an emergency setting. Methods: A prospective, observational study was conducted in a tertiary care Emergency Department over six months. Patients with ADHF were divided into two groups: the Early CPAP group (CPAP initiated within 30 minutes of presentation) and the Standard Therapy group (conventional management without early CPAP). Baseline characteristics, respiratory parameters, intubation rates, hospital stay, mortality, and 30-day readmission rates were compared. Statistical analysis was performed using SPSS, with significance set at p < 0.05. Results: The study included 158 patients (79 per group) with comparable baseline characteristics. The Early CPAP group showed significant improvements in respiratory parameters within two hours: higher SpO₂ (95% vs. 89%, p < 0.001), lower respiratory rate (20 vs. 24 breaths/min, p < 0.001), and improved pH (7.38 vs. 7.32, p < 0.001). Intubation rates were lower in the Early CPAP group (5% vs. 15%, p = 0.03), and both ED stay (5.8 vs. 7.1 hours, p < 0.001) and hospital stay (6.5 vs. 8.0 days, p < 0.001) were shorter. Mortality and readmission rates were lower but not statistically significant. Conclusion: Early CPAP therapy significantly improves respiratory function and reduces intubation rates and hospital stays in ADHF patients, supporting its use as an effective intervention in emergency settings. Further studies are needed to assess long-term outcomes.